Republic, religion and freedom: The Church and the Popular Front - Navarro de La Fuente, Santiago (Historia y Política, 2019)
After the victory of the Popular Front in February 1936, the Church needed to accept its failure to get the Spanish Constitution and all harmful laws amended. A new threatening period of time full of risk had risen. This paper analyzes how the Holy See managed the position of the Church in Spain during that period. The study of the diplomatic documents between Spain and the Holy See revealed a balanced position of the central government of the Church about the main issues debated in Spain, which may differ from some traditional beliefs. Beside protesting the attacks received and claiming the amendment of those hostile laws, the Holy See wanted to get closer to the moderate left in social politics, rejecting the CEDA position in this sense. In search of guarding its interest, the Church was claiming their legitimate rights and this would be an evidence of its adaptation to the democratic procedures.
Keywords: Church; Popular Front; Second Republic; Holy See; Spain